Polymorphisms and dental age in non-syndromic cleft lip and palate: a cross-sectional study - Gabriela Fonseca-Souza; Lhorrany Alves-Souza; Maria Angélica Hueb de Menezes-Oliveira; Nikolaos Daratsianos; Svenja Beisel-Memmert; Christian Kirschneck; Rafaela Scariot; Juliana Feltrin-Souza; Erika Calvano Küchler (BMC Pediatrics)
Abstract Background Children with non-syndromic cleft lip with or without palate (CL ± P) may present alterations in dental development. The purpose of this cross-sectional study was to compare the dental age (DA) between children with and without CL ± P, and whether single nucleotide polymorphisms (SNPs) in genes encoding growth factors are associated with DA variations. Methods Children aged between 5 and 14 years with and without CL ± P were recruited to participate in this study. DA was evaluated by calibrated examiners (kappa > 0.80) using the method proposed by Demirjian et al. (1973). Genomic DNA was extracted from buccal cells, and SNPs in Epidermal Growth Factor (EGF) – rs4444903 and rs2237051, Epidermal Growth Factor Receptor (EGFR) – rs2227983 –, Transforming Growth Factor Beta 1 (TGFB1) – rs1800470 and rs4803455 –, and Transforming Growth Factor Beta Receptor 2 (TGFBR2) – rs3087465 – were genotyped by real-time polymerase chain reactions using the TaqMan assay. The Student T-test was used to compare the variations in DA between the phenotypes “with CL ± P” and “without CL ± P”, and the ANOVA two-way test was performed to compare the variations in DA among the genotypes (α = 0.05). A post-hoc analysis was performed using Bonferroni correction. Results Two hundred and nine (n = 209) children (100 with CL ± P and 109 without CL ± P) with a mean chronological age of 8.66 years – standard deviation (SD) = 1.92 – were included. The group with CL ± P demonstrated a significantly delayed DA (mean=-0.23; SD = 0.71) compared to the group without CL ± P (mean=-0.01; SD = 0.88) (p = 0.049). Genotype distributions were in Hardy-Weinberg equilibrium. The SNP rs4803455 in TGFB1 was significantly associated with DA variations in children without CL ± P (p < 0.01). In the group with CL ± P, no significant differences in DA were observed among the genotypes. Conclusion Children with CL ± P presented delayed DA compared with children without CL ± P. The SNP rs4803455 in TGFB1 is associated with variations in DA in children without CL ± P.